Isolation of lupeol from Grewia lasiocarpa stem bark: Antibacterial, antioxidant, and cytotoxicity activities - Nneka Akwu; Yougasphree Naidoo; Moganavelli Singh; Sadashiva Channangihalli Thimmegowda; Nirasha Nundkumar; Johnson Lin (Society for Indonesian Biodiversity, 2020)
Abstract. Akwu N, Naidoo Y, Singh M, Thimmegowda SC, Nundkumar N, Lin J. 2020. Isolation of lupeol from Grewia lasiocarpa stem bark: Antibacterial, antioxidant, and cytotoxicity activities. Biodiversitas 21: 5684-5691. Lupeol a pentacyclic triterpenoid, was extracted from the stem bark of Grewia lasiocarpa. Stem bark was macerated with chloroform (CHCl3) at 25 ± 2°C, and then purified using a silica gel column. The mobile phase was hexane (100%) and hexane: ethyl acetate (80:20) as the mobile phase. The structure of lupeol was identified by 1HNMR, and 13C NMR spectral data, compared with reported data. The antibacterial, antioxidant and cytotoxicity activities of lupeol were evaluated using agar-well diffusion against six clinic bacteria isolates, namely Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853), Klebsiella pneumoniae (ATCC 314588), and Salmonella typhimurium (ATCC 14026) Gram-positive bacteria: Staphylococcus aureus (ATCC 25923), methicillin-resistant Staphylococcus aureus (MRSA) (ATCC BAA-1683). The antioxidants assays were performed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP). Cytotoxicity activity was carried out by MTT (3-(4,5-dimethylthiazol)-2,5-diphenyl tetrazolium bromide) assay was carried out against HEK293 (human embryonic kidney), HeLa (cervical carcinoma), and MCF-7 (breast adenocarcinoma) cell lines. The concentration range of lupeol was 240-15 µg/mL. Lupeol at the concentration of 240 and 120 µg/mL have no antibacterial activity against Methicillin-resistant Staphylococcus aureus (MRSA) (ATCC BAA-1683). The antioxidant activity was dose-dependent, while cytotoxic activities were observed in HEK293, HeLa, and MCF-7 cells. This study was the first report on the extraction, isolation, and biological activities of lupeol, from the stem bark of G. lasiocarpa.